Phosphoinositide Binding to the Substrate Regulates Susceptibility to Proteolysis by Calpain - Sprague, Chelsea R. (American Society for Biochemistry and Molecular Biology, 2008)
Calpain-mediated proteolysis regulates cytoskeletal dynamics and is altered during aging and the progression of numerous diseases or pathological conditions. Although several cytoskeletal proteins have been identified as substrates, how localized calpain activity is regulated and the mechanisms controlling substrate recognition are not clear. In this study, we report that phosphoinositide binding regulates the susceptibility of the cytoskeletal adhesion protein α-actinin to proteolysis by calpains 1 and 2. At first, α-actinin did not appear to be a substrate for calpain 2; however, phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P(3)) binding to α-actinin resulted in nearly complete proteolysis of the full-length protein, producing stable breakdown products. Calpain 1 was able to cleave α-actinin in the absence of phosphoinositide binding; however, PtdIns(3,4,5)P(3) binding increased the rate of proteolysis, and phosphatidylinositol 4,5-diphosphate (PtdIns(4,5)P(2)) binding significantly inhibited cleavage. Phosphoinositide binding appeared to regulate calpain proteolysis of α-actinin by modulating the exposure of a highly sensitive cleavage site within the calponin homology 2 domain. In U87MG glioblastoma cells, which contain elevated levels of PtdIns(3,4,5)P(3), α-actinin colocalized with calpain within dynamic actin cytoskeletal structures. Furthermore, proteolysis of α-actinin producing stable breakdown products was observed in U87MG cells treated with calcium ionophore to activate the calcium-dependent calpains. Additional evidence of PtdIns(3,4,5)P(3)-mediated calpain proteolysis of α-actinin was observed in rat embryonic fibroblasts. These results suggest that PtdIns(3,4,5)P(3) binding is a critical determinant for α-actinin proteolysis by calpain. In conclusion, phosphoinositide binding to the substrate is a potential mechanism for regulating susceptibility to proteolysis by calpain.